Successful Treatment of Hemorrhagic Bullous Henoch-Schönlein Purpura with Oral Corticosteroid: A Case Report - Celebi Kocaoglu; Ramazan Ozturk; Yasar Unlu; Fatma Tuncez Akyurek; Sukru Arslan (Case Reports in Pediatrics)
Henoch-Schönlein purpura (HSP) is a vasculitis of small-sized blood vessels, resulting from immunoglobulin-A-mediated inflammation. It is the most common acute systemic vasculitis in childhood and mainly affects skin, gastrointestinal tract, joints, and kidneys. The characteristic rash of HSP consists of palpable purpuric lesions 2 to 10 mm in diameter concentrating in the buttocks and lower extremities. The occurrence of hemorrhagic bullae in children with HSP is rarely encountered. This report describes a 4.5-year-old female patient with HSP associated with hemorrhagic bullous lesions.